Evaluasi Data GPM-IMERG (Global Precitipation Measurement - Integrated Multi-Satellite Retrieval For GPM) di Provinsi NTB - Imam Kurniawan (Megasains, 2022)
Global Precipitation Measurement - Integrated Multi-Satellite Retrieval for GPM (GPM-IMERG) product data has been tested. Evaluation has been carried out for the 2017 rainfall data at 31 rainfall observation stations in Nusa Tenggara Barat province. Tests were carried out using statistical and categorical analysis methods. Based on the results of statistical analysis, it was found that the rainfall estimation results in the GPM-IMERG model were overestimates where the bias was positive. From the analysis of ten-days rainfall data, it was found that a fairly high correlation between the GPM-IMERG data and the observation data at 31 rainfall station, with an average correlation value of 0,64. The highest correlation occurs in the Sekotong area with a correlation value of 0,85. High correlation also occurs at BMKG stations with values ranging from 0,67 to 0,83. Meanwhile, for categorical analysis, it also got a fairly good value with an average accuracy value of 0,75 and the POD value is 0,78. The highest accuracy value occurs in the Kediri area, which is based on BMKG Climatology Station data with a value of 0,82. Based on these results, the GPM-IMERG can be considered to be used as a reference for rain data in conducting climate analysis.